Research on the ways of the pectin extraction from the potatoes - Pastukh, Hanna; Grytsay, Julia; Hrabovskyi, Yevhen (My University, 2013)
The results of research methods extracting pectin from potato pulp, leaving the production of starch potatoes. By planning the experiment was conducted research summarized, analyzed and considered their results, carried out the statistical processing of experimental data, the optimum technological conditions for obtaining pectin from potato and its structure studied by means of infrared spectroscopy.Наведено результати дослідженнь способів вилучення пектину з картопляної мезги, відходу виробництва крохмалю з картоплі. Шляхом планування експерименту було проведено узагальнені дослідження, проаналізовано та враховано їх результати, проведено статистичне оброблення експериментальних даних, визначено оптимальні технологічні умови одержання пектину з картоплі та досліджено його структуру за допомогою ІЧ-спектроскопії.
Keywords: potato pulp; optimal parameters; pectin; картопляна мезга; пектин; оптимальні параметри; картофельная мезга; оптимальные параметры; пектин